Formulação e testes de funcionalidade de bebida simbiótica a base de polpa de café, amêndoas de jerivá e farinha de yacon - Sousa , Fernanda Maria de (2022)
Due to the growing demand for foods that are beneficial to health and with low environmental impact, the fermentation industry has been betting on studies involving alternative plant sources such as agricultural processing residues, such as coffee pulp, and PANC's (Unconventional Food Plants), like jerivá almonds. The objective of this project was to optimize the fermentation process of a medium based on extracts of arabica coffee pulp (EPC), jerivá almonds (EAJ) and yacon flour (FrY) with probiotics, through a sequential planning strategy applying initially the Plackett and Burman and then the DCCR (Central Composite Rotational Design). 50 mL of different formulations were fermented in triplicate with Lactobacillus rhamnosus and Bifidobacterium longum at 37ºC in anaerobic conditions, brought to pH≈4.5 to obtain a sensorially balanced drink. After analysis by Plackett and Burman, it was concluded that the most important independent variables were EPC and FrY, as they reduced the fermentation time of the symbiotic drink (t≈20h), with good cell growth (≈5 LogUFC.mL-1) , consumption of total (CAT) and reducing (CAR) sugars (max=68.0 g/L and 43.2 g/L, respectively), production of exopolysaccharides (max=0.9 g/L) and organic acids ( max=1.08g/L). The DCCR results indicated that the response variables Time; TotalGrow; GrowLR; GrowBL; CAT; PAT and Color parameters L*, a*, b* showed a good fit of the model at 95% confidence (p<0.05). The best prototypes of symbiotic drink contained 10 to 14 % w/v of Yacon Flour, 8 to 16 % v/v of coffee pulp extract, 5% v/v of functional coffee pulp extract and 17.5 % v/v of jerivá almond extract, with the best cell counts (≈13 LogUFC.mL-1). By validating the models under these conditions, it was possible to predict the fermentation time (around 20h) and CresTotal (around 5.1 Log CFU.mL-1); CrescLR (around 5.3 LogUFC.mL-1) and CrescBL (around 5.02 LogUFC.mL-1). Of the DCCR treatments, the one that showed the highest production of lactic acid (5.3 g/L) (HPLC) and the highest concentration of live cells (48.45%) (Flow Cytometry) at the end of fermentation was Treatment 4, (22.1%m/v of FrY and 25.6%v/v of EPC), with postbiotic compounds being identified in all treatments evaluated with a maximum of 26.15% in Treatment 5 (5%m/v of FrY and 15 %v/v EPC), which guarantees beverage functionality. In vitro functional tests showed higher probiotic counts in the first 3 hours of digestion (8.1 LogUFC.mL-1) with a drastic drop after 4 hours of digestion (5.5 LogUFC.mL-1) and the ability to Cell adherence to gut-associated lymphoid tissue ranged from low (%H=32.07 Treatment 1 of Validation) to medium (%H=39.31 of Treatment 2 of Validation).